Development of a pharmaceutical management plan for medicinal gases in a public university hospital in Belém (Research, Society and Development, 2023)
Objective: Develop a plan for the management, monitoring and use of GM in the HUJBB. Material and methods: This is an exploratory and observational field research with a qualitative approach, carried out with a situational diagnosis, using a checklist with 28 items according to norms and legislation on medicinais gases. It was considered as a sample, the places that store and distribute the GM. The results were treated with the management tools, Swot Matrix and 5W2H, in different phases: identification and data analysis. Results: Of the 28 items, 9 items did not meet the standards and legislation: Storage area, receipt of GM, identification of empty cylinders, cylinder valve protection helmet, cylinder labels, severe corrosion and emergency alarms in care units. Through the Swot Matrix, the strengths and weaknesses, threats and opportunities were observed and by the 5W2H method, 7 corrective action plans were proposed for the adjustments of the items. Conclusion: This work was developed to meet the needs of reorganizing the Management of GM by the Pharmacy Sector at HUJBB. In this sense, it was observed that there was still a lack of actions on the part of the institution so that the standards and precepts of quality were actually a reality in the hospital. Pharmacists are expected to adopt the informative instrument generated by this research, Manual of Guidance on Medicinal Gases, on the main issues inherent to GM and also, it could be expanded to other university hospitals, as a management and monitoring tool.